Usability of Self-Management for Amputee Rehabilitation using Technology (SMART): An online self-management program for users with lower limb loss. Issue 2 (22nd April 2023) - Esfandiari, Elham; Miller, William C.; King, Sheena
Abstract : Background: Individuals with lower limb loss (LLL) need education to adapt to their amputation. Self-management programs provide education and supportive skills to manage health-related physical and psychological challenges. eHealth technologies, such as online platforms, are increasing access to educational resources. We designed an online self-management program for individuals with LLL called Self-Management for Amputee Rehabilitation using Technology (SMART); however, before evaluating its efficacy, we wanted to understand its appropriateness in the target population. Objective: To assess the usability of SMART among individuals with LLL. Study Design: The study used a concurrent and retrospective think-aloud process. Methods: Individuals with LLL, aged 18 years or older (n = 9), reviewed the modules during an online video conferencing session with an assessor. SMART included four stakeholder-informed modules with 18 total sections. Participants were asked to think aloud while completing 11 SMART tasks, such as entering SMART, goal setting, finding skin care, and reading the content of 10 sections, including limb care, diet, fatigue, and energy. The interviews were transcribed verbatim and analyzed using directed content analysis. Results: The median age was 58 (range: 30–69) years. Overall, SMART was perceived as straightforward, easy to navigate, and an accessible resource for education and skills. Difficulties were identified with navigation (e.g. skipping the "Foot care for diabetes" section), presentation (e.g. unclear audio), and language (e.g. pistoning and contracture). Conclusions: SMART was redesigned to address the usability issues. The next step is to explore the perceived usefulness of SMART for content and intention to use.